Comparison of Transvaginal and Transabdominal Ultrasound in the Diagnosis of Adnexal Masses - Muhammad Wasif Iqbal, Iffat Batool, Rabia Ashraf, Amina Noor, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Our research aims to compare the diagnostic efficacy of transvaginal and transabdominal ultrasonography for detecting adnexal masses. Study Design: A Comparative study Place and Duration: Conducted at Central Park Medical College, Lahore, during from the period August 2021 to January 2022. Methods: This study included 84 women. Once written consent has been obtained, we involve consideration such as aging, gender, menstrual abnormalities (Oligomenorrhea / Menstrual periods), infertility, recurrent multiple miscarriages, series of acts, acne vulgaris, and obesity. The ultrasound data included the location, size, borders, hypoechoic and dilatation of ovary lesions. Group M had 42 patients and underwent for transvaginal ultrasound, whereas group N had transabdominal ultrasound with MRI. Using histological results (positive/negative), frequency of adnexal mass among all cases were compared. SPSS 20.0 analyzed all data. Results: In group M mean parity was 3.5±2.13 and in group N parity was 2.9±4.13. Most common complaint among all cases was infertility and irregular cycle. We found that frequency of adnexal mass in group M was lower than that of group N. It was determined that the specificity, positive predictive value, and negative predictive value of transvaginal sonography were all lower than those of transabdominal sonography. Conclusion: In this study, we came to the conclusion that abdominal ultrasonography combined with MRI was superior in terms of its usefulness and efficacy in identifying adnexal masses with genuine levels of both specificity and sensitivity. Keywords: Accuracy, Transvaginal ultrasonography,Transabdominal ultrasonography, Adnexal Masses, Complications,